2019
DOI: 10.1021/acsomega.9b00969
|View full text |Cite
|
Sign up to set email alerts
|

Designing Nanoporous Membranes through Templateless Electropolymerization of Thieno[3,4-b]thiophene Derivatives with High Water Content

Abstract: In this work, we present the synthesis of original thieno[3,4- b ]thiophene monomers with rigid substituents (e.g., perfluorinated chains, and aromatic groups) and demonstrate the ability to prepare nanotubular and nanoporous structures via templateless, surfactant-free electropolymerization in organic solvents (dichloromethane). For the majority of synthesized monomers, including a significant amount of water in the electropolymerization solvent leads to the formation of nanoporous memb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 36 publications
2
31
0
Order By: Relevance
“…84,85 Very recently, we have studied the influence of water on the surface morphology of electrodeposited polymers from thieno-[3,4-b]thiophene derivatives. 86,87 It has been demonstrated that with a significant amount of water in dichloromethane (dichloromethane saturated with water vs commercial dichloromethane), the surface morphology is drastically changed, e.g., from densely packed spherical particles to nanoporous membrane structures (with pores of d ∼ 100−300 nm) 86 or from smooth or treelike surfaces to hollow spherical or coral-like structures. 87 This is likely due to the formation of a large amount gas bubbles (O 2 and H 2 ) during electropolymerization in the dichloromethane/water system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…84,85 Very recently, we have studied the influence of water on the surface morphology of electrodeposited polymers from thieno-[3,4-b]thiophene derivatives. 86,87 It has been demonstrated that with a significant amount of water in dichloromethane (dichloromethane saturated with water vs commercial dichloromethane), the surface morphology is drastically changed, e.g., from densely packed spherical particles to nanoporous membrane structures (with pores of d ∼ 100−300 nm) 86 or from smooth or treelike surfaces to hollow spherical or coral-like structures. 87 This is likely due to the formation of a large amount gas bubbles (O 2 and H 2 ) during electropolymerization in the dichloromethane/water system.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…[33] The water content of the polymerization solvent also plays a huge part in the morphology of the resulting nanostructures, increasing their porosity. [34,35] The water indeed reacts during electropolymerization forming gas bubbles that can act as a softtemplate for the polymer deposition. It has been recently demonstrated that reverse micelles are formed in the electropolymerization solvent, and that these micelles also participate to the formation of a soft template, leading to porous nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the nanotube formation is highly affected by H 2 O content because it changes the amount of released O 2 and/or H 2 bubbles. Indeed, the influence of H 2 O was already studied in the literature, [ 29,31 ] for example, by adding different amount of H 2 O and it was shown that the increase in H 2 O can often increase the number of nanotubes or other porous structures. [ 31 ]…”
Section: Introductionmentioning
confidence: 99%
“…Very recently, by a judicious choice in monomer and H 2 O content, the templateless electropolymerization process in organic solvent such as dichloromethane (CH 2 Cl 2 ) has been proposed as an efficient method to prepare extremely well‐controlled porous nanostructures such as vertically aligned nanotubes. [ 26–33 ] Trace H 2 O naturally present in solution are responsible for the formation of gas bubbles (O 2 and/or H 2 ). The method does not require any acid or surfactant but the monomer has to play the role of the surfactant in stabilizing gas bubbles during electropolymerization.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation